Management of Bronchiolitis with or without Antibiotics A Randomized Control Trial - Mazumder, Md Jashim Uddin; Hossain, Mohammad Monir; Kabir, ARM Luthful (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Background: There has been epidemics of bronchiolitis in the recent years in Bangladesh. Bronchiolitis is mostly (95%) a viral disease in infants and young children but being treated with antibiotics in 99% of cases in our situation. Antibiotic has little role in the management of bronchiolitis. Very few randomized control trials without antibiotics in the management of bronchiolitis have so far been done. Objectives: To evaluate the outcome of bronchiolitis with or without antibiotics in a hospital setting. Methods: A randomized control trial was done during one winter season of 2005 with all cases of bronchiolitis attending a teaching hospital of Dhaka, Bangladesh. Sample size was selected conveniently. One hundred twenty six consecutive cases (one month up to 2 years) with clinical bronchiolitis (runny nose followed by wheeze, cough, breathing difficulty perceived by caregiver, chest indrawing and rhonchi on auscultation) who attended the hospital were enrolled in the study. Detailed history and clinical examination were done and the children were randomized into 3 groups: (1) parenteral antibiotic group, paren AB (30) treated with supportive management and IV ampicillin, (2) oral antibiotic group, oral AB (33) treated with supportive management and oral erythromycin and (3) no antibiotic group, no AB (63) treated with supportive management only. The children were managed both in indoor and outdoor but very sick patients particularly those having oxygen saturation <90% were admitted into the hospital or excluded from the study (if not agreed for hospitalization). Oxygen therapy was given to cases having oxygen saturation < 90% and IV fluid (10% dextrose in 0.225% NaCl) was given to severely distressed children. Tube feeding was given to children who were unable to take milk by mouth but not very sick deserving IV fluid. Antibiotic was given according to the protocol. All children were followed up for 23 parameters, hospitalized cases were observed 8 hourly and outdoor (OPD) cases twice in the morning and at noon. Outcome measures were breathing difficulty, feeding difficulty, social smile, fast breathing (R/R > 50/m), hypoxia (oxygen saturation <95%), wheeze, rhonchi and crepitation. Verbal consent of the parents was taken before the study. Whenever patients condition became worse with the given treatment, the children was taken out of the study and more intensive management was given. Parents were also at liberty to discontinue the treatment process whenever they wanted irrespective of the reasons. Results: Out of enrolled 126 children with bronchiolitis 104 (82.5%) improved and were discharged safely. The improved children in different groups were as follows: paren AB 29 (27.8%), oral AB 32 (30.7%) and no AB 43 (41.3%). Total 22 cases were excluded from the study, o1 from paren AB, 01 from oral AB and 20 from no AB group. Among them 18 were OPD cases, did not turn out on regular follow up, 2 cases left hospital on DORB and 2 cases were excluded from no antibiotic group for persistence of breathing difficulty and crepitation in the lung and treated with antibiotics. There was no death. Mean TWBC count was around 8500/cmm in all the groups. The mean value of neutrophil and lyphocytes were 33% and 61% respectively. Radiologically about 70% cases had hyperinflation, 52% cases had hypertranslucency and 56% cases had streaky densities. Hundred percent children had breathing difficulty at the time of inclusion into the study in all the groups. The decrement of breathing difficulty was gradual in all the groups and on day 5 only 27% in paren AB , 25% in oral AB and 34% in no AB group had breathing difficulty (p o.66). About 50% children had feeding difficulty at the beginning of study in all the groups. The decrement of feeding difficulty was found rapid and similar in all the groups and there was no feeding difficulty on day-5 in all the groups. Only 34% children in paren and oral AB group and 30% in no AB group had social smile on day-1. On day-3 about 90% of children of all the groups started smiling in spite of having fast breathing and chest in drawing. About 91% children had tachypnea (RR >50/m) at the time of inclusion into the study. The decrement of fast breathing was gradual and similar in all the groups and on day five only about 10% children had fast breathing and it was equal in all the groups (p0.05). About 54% children had hypoxia during inclusion in all the groups (p0.49). The improvement of hypoxia was rapid and similar in all the groups and on day-5 only 6.7% had hypoxia. Hundred percent children of all groups had wheeze at the beginning of the study. The decrement of wheeze was gradual and similar in all groups. On day five total 15% children had wheeze and it was almost equal in all the groups (p0.82 ). The decrement of crepitations in all the groups was also gradual. During inclusion into the study about 60% children had crepitations and it was almost equal in all the groups and on day five about 14% children had crepitations in all the groups (p0.97). Conclusion: The recovery of bronchiolitis managed with supportive therapy alone was found similar to those treated with combined supportive therapy and antibiotics (either oral or parenteral). DOI: 10.3329/jbcps.v27i2.4248 J Bangladesh Coll Phys Surg 2009; 27: 63-69